English syntactic acquisition among Malay-English bilingual primary school students - Mohamed Salleh, Rabiah Tul Adawiyah (2022)
In the original version of Processability Theory (PT) by Pienemann (1998), the development of learners’ L2 morphology and syntax are analysed in the same hierarchy/schedule. In Pienemann, Di Biase and Kawaguchi (2005), the analysis of learners’ L2 syntax, inspired by developments in Lexical Functional Grammar (Bresnan 2001), was extended to encompass discourse-pragmatic functions and lexical mapping, which account for higher levels of complexity. These aspects were further expanded by Bettoni and Di Biase (2015) leading to the Prominence Hypothesis and some adjustments regarding the Lexical Mapping Hypothesis. The current study presents the acquisition of English syntax among Malay-English bilingual primary school children from the latter developments. Five nine-year-old children, who have attended the same primary school which employed the Standard Based Curriculum for Primary Schools (KSSR) syllabus for 2 years (i.e., since they were 7 years old) became the informants for this study. The speech output of the children was elicited through two communicative tasks. Based on the Prominence Hypothesis, results demonstrate that the children used canonical word order (SVO) and had progressed to the XPDF canonical word order stage (TOPXP SVO) but had not yet reached the non-canonical word order (TOPXP marked orders). From The Lexical Mapping Hypothesis standpoint, the children were found to use the default thematic mapping (Agent/experiencer mapped on SUBJ, patient/theme mapped on OBJ) as well as the default mapping with additional arguments (Agent/experiencer mapped on SUBJ, patient/theme mapped on OBJ, and other members of the a-structure hierarchy such as goals and locatives, mapped on OBL) but they have not reached the non-default mapping structure (e.g. passives). These findings are significant because these newer PT hypotheses are tested for the first time on the English L2 syntax of bilingual Malay-English children and because of their implications for English curriculum development for Malaysia’s primary schools.